2020
DOI: 10.1007/s42399-020-00585-6
|View full text |Cite
|
Sign up to set email alerts
|

Into the Storm: a Mixed Methods Evaluation of Reasons for Non-attendance of Appointments in the Free Clinic Setting

Abstract: Non-attendance of healthcare appointments impact individual health outcomes and the capacity and financial stability of clinics. While non-attendance of appointments has been associated with a variety of factors, interventions to increase attendance have had mixed success. The most widely used intervention, reminder systems like phone calls or text messages, generally improves attendance rates but is insufficient for many clinics as a sole intervention. This study of underresourced patients who did not attend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…If proven effective, this program has important implications for patients who are isolated by either their physical disabilities, distant living location or the pandemic situation, which may be recurrent. In addition, given that most of the DM patients are full-time workers, to prevent the loss of work and salary being cut, report showed that they have the tendency to skip the medical appointment occasionally [ 33 , 34 ]. Non-attendance not only has an impact on patients’ health outcomes, but also influence the capacity and financial stability of clinics.…”
Section: Discussionmentioning
confidence: 99%
“…If proven effective, this program has important implications for patients who are isolated by either their physical disabilities, distant living location or the pandemic situation, which may be recurrent. In addition, given that most of the DM patients are full-time workers, to prevent the loss of work and salary being cut, report showed that they have the tendency to skip the medical appointment occasionally [ 33 , 34 ]. Non-attendance not only has an impact on patients’ health outcomes, but also influence the capacity and financial stability of clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Many healthcare professionals were concerned about the emotional health of adults with chronic illness at the outbreak of the pandemic [ 6 , 7 ]. Stress and anxiety are well-known risk factors for maladaptive coping (smoking, substance use, unhealthy eating habits and sedentary behavior) [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ], inadequate treatment adherence [ [18] , [19] , [20] , [21] , [22] ], reduced self-efficacy [ [23] , [24] , [25] ], avoidance of healthcare visits [ [26] , [27] , [28] ], and worse health outcomes [ [29] , [30] , [31] ]. In addition, the potential negative health consequences associated with limited availability and access to healthcare services were cited as a significant concern [ 32 ].…”
Section: Introductionmentioning
confidence: 99%